A somatosensory cortex input to the caudal dorsolateral striatum controls comorbid anxiety in persistent pain. Issue 2 (February 2020) - Jin, Yan; Meng, Qian; Mei, Lisheng; Zhou, Wenjie; Zhu, Xia; Mao, Yu; Xie, Wen; Zhang, Xulai; Luo, Min-Hua; Tao, Wenjuan; Wang, Haitao; Li, Jie; et al.
Abstract : Abstract: Chronic pain and anxiety symptoms are frequently encountered clinically, but the neural circuit mechanisms underlying the comorbid anxiety symptoms in pain (CASP) in context of chronic pain remain unclear. Using viral neuronal tracing in mice, we identified a previously unknown pathway whereby glutamatergic neurons from layer 5 of the hindlimb primary somatosensory cortex (S1) (Glu S1 ), a well-known brain region involved in pain processing, project to GABAergic neurons in the caudal dorsolateral striatum (GABA cDLS ). In a persistent inflammatory pain model induced by complete Freund's adjuvant injection, enhanced excitation of the Glu S1 →GABA cDLS pathway was found in mice exhibiting CASP. Reversing this pathway using chemogenetic or optogenetic approaches alleviated CASP. In addition, the optical activation of Glu S1 terminals in the cDLS produced anxiety-like behaviors in naive mice. Overall, the current study demonstrates the putative importance of a novel Glu S1 →GABA cDLS pathway in controlling at least some aspects of CASP. Abstract : Supplemental Digital Content is Available in the Text.A novel neural pathway in mice that projects directly from the primary somatosensory cortex to the caudal dorsolateral striatum controls anxiety-like behaviors in chronic pain.